Effect of Internal Pressure on Incipient Ferroelectricity of Nanoconfined Water Molecules Observed in Hydrothermally Grown Beryl Crystals. Issue 3 (20th December 2022) - Gorshunov, Boris; Abalmasov, Veniamin; Uskov, Vladimir; Chan, Yuk Tai; Uykur, Ece; Abramov, Pavel; Dressel, Martin; Thomas, Victor; Savinov, Maxim
Abstract : Quasistatic dielectric permittivity of D2 O type I molecules (electric dipole moment perpendicular to the crystallographic c ‐axis) within hydrothermally grown beryl crystals characterized by different internal pressure and content of D2 O type II molecules (dipole moment parallel to the c ‐axis) is measured at temperatures 4–300 K. All crystals are found to display quantum paraelectric behavior of the D2 O‐I molecular subsystem permittivity, that is, permittivity growth while cooling from room temperature followed by saturation below 15–40 K. Processing the data with the Barrett expression shows that excess internal pressure and excess content of D2 O‐II molecules lead to an increase in quantum temperature T 1 and a decrease in the Curie constant C, with the Curie temperature T C remaining unchanged. The discovered strengthening of quantum effects (growth of T 1 ) within an ensemble of dipole–dipole‐coupled D2 O‐I molecules is associated with an enhanced azimuthal tunneling of these molecules within the hexagonal localizing potential. The data indicate the possibility of using crystal growth conditions to "tune" the strength of quantum effects in the network of polar water molecules, which provides a workbench for further studies of exotic phases of a lattice of coupled "point" electric dipoles. Abstract : Temperature‐dependent (4–300 K) quasistatic (1 Hz) dielectric permittivity of a network of polar water molecules confined within beryl crystal displays quantum paraelectric behavior. The role of quantum effects increases with the growth of internal pressure, thus opening up perspectives for the studies of a unique class of quantum ferroelectrics composed by "point" dipoles.